International service trade and its implications for human resources for health: a case study of Thailand - Pitayarangsarit Siriwan; Pachanee Cha-aim; Wibulpolprasert Suwit; Hempisut Pintusorn (BMC, 2004)
Abstract This study aims at analysing the impact of international service trade on the health care system, particularly in terms of human resources for health (HRH), using Thailand as a case study. Information was gathered through a literature review and interviews of relevant experts, as well as a brainstorming session. It was found that international service trade has greatly affected the Thai health care system and its HRH. From 1965 to 1975 there was massive emigration of physicians from Thailand in response to increasing demand in the United States of America. The country lost about 1,500 physicians, 20% of its total number, during that period. External migration of health professionals occurred without relation to agreements on trade in services. It was also found that free trade in service sectors other than health could seriously affect the health care system and HRH. Free trade in financial services with free flow of low-interest foreign loans, which started in 1993 in Thailand, resulted in the mushrooming of urban private hospitals between 1994 and 1997. This was followed by intensive internal migration of health professionals from rural public to urban private hospitals. After the economic crisis in 1997, with the resulting downturn of the private health sector, reverse brain drain was evident. At the same time, foreign investors started to invest in the bankrupt private hospitals. Since 2001, the return of economic growth and the influx of foreign patients have started another round of internal brain drain.